2012
DOI: 10.1016/j.jvs.2012.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Use of a postoperative insulin protocol decreases wound infection in diabetics undergoing lower extremity bypass

Abstract: Strict glucose control in patients undergoing coronary bypass grafting has been shown to decrease infectious complications, arrhythmias, and mortality. Our objective was to determine if strict glucose control reduced morbidity after lower extremity bypass (LEB). Methods: A prospective pilot study at a single institution within the Vascular Study Group of New England was conducted from January 2009 to December 2010. Patients with diabetes and without undergoing LEB were placed on an intravenous (IV) insulin inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…They concluded that strict glucose control with a postoperative insulin infusion protocol significantly decreased the incidence of postoperative in-hospital wound infection in the diabetic population but did not lower other postoperative complications. 20 An unexpected finding from this analysis was that after multivariable adjustment, diabetes was not associated with increased infection risk but was associated with shorter hospital stays and decreased mortality. It has been previously reported that in-hospital hyperglycemia is a common finding and represents an important marker of poor clinical outcome and mortality in patients with and without a history of diabetes and that patients with newly diagnosed hyperglycemia have worse outcomes.…”
Section: Discussionmentioning
confidence: 78%
“…They concluded that strict glucose control with a postoperative insulin infusion protocol significantly decreased the incidence of postoperative in-hospital wound infection in the diabetic population but did not lower other postoperative complications. 20 An unexpected finding from this analysis was that after multivariable adjustment, diabetes was not associated with increased infection risk but was associated with shorter hospital stays and decreased mortality. It has been previously reported that in-hospital hyperglycemia is a common finding and represents an important marker of poor clinical outcome and mortality in patients with and without a history of diabetes and that patients with newly diagnosed hyperglycemia have worse outcomes.…”
Section: Discussionmentioning
confidence: 78%
“…O regime de controle glicêmico por meio ICI foi adotado em seis estudos primários (28,(32)(33)(34)(35)(36) . Uma pesquisa delimitou o controle glicêmico de 100-150mg/dL no perioperatório, usando o regime de ICI em pacientes com e sem diabetes, sendo que os resultados não apresentaram diferença estatisticamente significante na incidência de infecções pós-operatórias entre os grupos (28) .…”
Section: Discussionunclassified
“…Três pesquisas que os autores investigaram o controle glicêmico rigoroso foram conduzidas com diferentes níveis de glicemia alvo (34)(35)(36) . No estudo de coorte, ao final do primeiro ano de experiência, os dados apontaram diminuição da taxa anual de ISC em 50% (34) .…”
unclassified
See 1 more Smart Citation
“…Although some investigators offer data to support close glucose control via the use of insulin infusion in vascular surgery patients, 4,5 other investigators suggest that overly aggressive control may be harmful, 6 leading to higher rates of hypoglycemia and postoperative complications. This controversy has resulted in significant variation in strategies for managing perioperative glucose among diabetic patients undergoing vascular surgery.…”
mentioning
confidence: 99%